ANALISIS PENGGUNAAN ADJEKTIVA NOMINATIF DALAM BAHASA JEPANG (Berdasarkan Data Sintaksis Corpus) - Puspitosari, Dwi (Chi'e: Journal of Japanese Learning and Teaching, 2019)
This study aims to identify nominative adjectives in Japanese that are difficult to categorize based on the occurred changes when these words are produced along with the other words. For non-native Japanese learners, this has become a challenging issue. The main reason is the adjective that was classified into two categories in accordance with their changes, i.e., i-adjectives and na-adjectives. These adjectives presented different forms of change that had a tendency of transforming into nouns when collaborating with other nouns. Not only did learners in elementary and secondary level face the difficulties, but also those in upper levels did. The data in this study focused on adjectives with a high frequency of use that were collected from "Gendai Nihongo Kakikotoba Kinko Koopasu". The data was analyzed based on the use of adjectives in sentences taken from the corpus data, which underwent different forms of changes. The results of this study indicated that there were many adjectives that underwent different forms of changes and could be classified into multiple word classes. Penelitian ini bertujuan untuk mngidentifikasi kata sifat-kata sifat yang bersifat nominatif dalam bahasa Jepang yang sulit dikategorikan berdasarkan perubahan saat berhadapan dengan kata lain. Bagi pembelajar bahasa Jepang non-native speaker, hal seperti ini merupakan permasalahan yang dirasa sulit. Alasannya adalah karena kata sifat yang menurut perubahannya diklasifikasikan menjadi dua yakni kata sifat -i dan kata sifat -na, mengalami perubahan yang tidak seragam dan cenderung menjadi nomina saat dihadapkan dengan nomina. Tidak hanya pada pembelajar tingkat dasar dan menengah, pembelajar tingkat atas pun mengalami kesulitan. Pada penelitian ini, data akan difokuskan pada kata sifat dengan frekuensi pemakaian yang tinggi dan dikumpukan dari â€œGendai Nihongo Kakikotoba Kinko Koopasuâ€. Proses analisis data dilihat dari penggunaan kata sifat dalam kalimat diambil dari data corpus, yang mengalami perubahan tidak seragam. Hasil dari penelitian ini menunjukkan banyak kata sifat yang mengalami perubahan tidak seeragam dan dapat diklasifikasikan ke dalam kelas kata ganda.